STUDI SIFAT TERMAL BATUAN DAERAH LAPANGAN PANAS BUMI WAY RATAI BERDASARKAN PENGUKURAN METODE KONDUKTIVITAS TERMAL - Ryan Donovan; Karyanto Karyanto; Ordas Dewanto (Engineering Faculty Universitas Lampung, 2018)
Research on Way Ratai geothermal field has been done by measuring the thermal conductivity method. The thermal conductivity data is used to generate a map of the dispersion of heat conductively conductive rocks in the geothermal system. The result of measurement by thermal conductivity method in Way Ratai geothermal field is data of k (conductivity), Rt (thermal resistivity), and T (temperature). The value of the measured conductivity data in the geothermal field has range between 0.056-0.664 W/mK, the measured thermal resistivity value has range between 1.344-17.527mK/W, and the measured temperature value is between 22.68-52.59°C. The difference value of rock’s thermal conductivity is influenced by several factors, which is the existing geological structures in the field such as normal faults and lineaments, the presence of alteration, also the manifestation zone of hot water or hot vapor that caused from fumaroles.